Revisiting the Effect of Exchange Rates on Imports and Exports in South Africa. - Mpungose , Nonhlanhla; ngubane, mbongeni; Sekome, Mashapa (Acta Universitatis Danubius. Œconomica, 2023)
South African economic growth rely hardly on export of goods and services. Meanwhile imports are also part of the economic development package. Both imports and exports form part of the balance of payment equilibrium again it’s used to calculate terms of trade that could affect and be affected by the exchange rates. The study investigates the effect of exchange rates, economic growth and inflation on imports and exports via ADF cointegration approach to detect the existence of the equilibrium in the aforementioned variables. The secondary data stretched from 1994Q1 to 2021Q4 was employed. Furthermore, the terms of trade was included in the process, to explore the nexus between the terms of trade, economic growth, exchange rates and inflation via the VAR model. The study findings confirmed that the terms of trade have significant impact on exchange rates. The latter pass-through effects to inflation rates while growth is not highly affected by terms of trade but negatively affected by inflation and exchange rates. The study argue the policy makers to accelerate the volume of import via the labour intensive sectors to curb the high unemployment, reduce the trade deficit and accelerate growth.